As relações da União Européia-América Latina: do voluntarismo ao realismo / European Union-Latin American relations: from voluntarism to realism - Malamud, Andrés (Mural Internacional, 2011)
“Quem eu devo chamar se quiser ligar para a América Latina?” Não há qualquer organização regional que una todos os países da América Latina numa exclusividade. Como pode a América latina ser um ator internacional? O artigo debate as relações da União Europeia com a América Latina e Caribe, nos marcos do diálogo estabelecido em 1999 e em um cenário de uma organização latino-americana única e representante de fato dos países da região. ABSTRACT “Who should I speak to if I want to call Latin America;” There is no regional organisation that unites all the countries of Latin America exclusively. How can Latin America be an international player? This article discusses the relations between the European Union and Latin America and the Caribbean under the terms of the dialogue established in 1999 and under a scenario of a single Latin American organisation that actually represents the region’s countries. Palavras-chave: América Latina, União Europeia, regionalism e inter-regionalismo. Keywords: Latin America, European Union, regionalism and inter-regionalism. DOI: http://dx.doi.org/10.12957/rmi.2011.5378